2010
DOI: 10.1111/j.1365-3032.2009.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

A newly discovered sperm transport system in the female of Lygaeidae bugs

Abstract: In the female reproductive system of the relatively large hemipteran, the western conifer seed bug Leptoglossus occidentalis (Heidemann), a cuticle-lined tube extends medially along the surface of the vagina from the proximal end of the spermathecal complex anteriorly to the base of the common oviduct. This medial tube houses the proximal end of the spermathecal duct, thereby enabling the transport of material from the spermatheca at the distal end of the spermathecal complex, past the vagina (or bursa copulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Our investigations revealed a high degree of complexity in the organization of the spemathecal complex in M. histrionica, in accordance to what has already been described in other true bugs, particularly lygaeids (Gschwentner & Tadler 2000, Chiang 2010). However, we were unable to ind in M. histrionica a structure that can be related to the "medial tube" described by Chiang (2010) in Leptoglossus occidentalis (Heidemann) (Hemiptera: Coreidae).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our investigations revealed a high degree of complexity in the organization of the spemathecal complex in M. histrionica, in accordance to what has already been described in other true bugs, particularly lygaeids (Gschwentner & Tadler 2000, Chiang 2010). However, we were unable to ind in M. histrionica a structure that can be related to the "medial tube" described by Chiang (2010) in Leptoglossus occidentalis (Heidemann) (Hemiptera: Coreidae).…”
Section: Discussionsupporting
confidence: 69%
“…The functional signi icance of such complicated structures could be interpreted in terms of cryptic female choice, i.e. occurring after insemination, as already proposed by Chiang (2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many workers have studied the morphology of spermatheca of orthopteran insects and some have published histology of spermatheca of orthopteroid insects (Ahmed and Gillott, 1981;Dirsh, 1957;Gupta, 1948;Kevan et al, 1969;Kharibam et al, 1982;Pal and Ghosh, 1982;Qadri, 1940;Slifer, 1939Slifer, , 1940aSlifer, , 1940bSlifer, , 1940cSlifer, , 1943aSlifer, , 1943b. Previously some workers also reported that in some orthopteroid insects, spermathecal gland is lacking (Chiang, 2010;Gschwentner and Tadler, 2000). The present paper reports about the studies on the epiphallus and spermatheca in some species of the genus Acrotylus (Acridoidea: Orthoptera) of Pakistan.…”
Section: Introductionmentioning
confidence: 82%
“…Rather than resembling those arthropods which make encapsulated spermatophores that harden before they are inserted into the bursa copulatrix of the female [46], the Reduviidae are more closely related to insect species which lack spermatophores and deliver the semen by using a long intromittent organ that the male inserts through an insemination duct to the spermatheca [44]. In R. prolixus, the spermathecae are attached directly to the common oviduct so that no insemination tube is required since this location is very close to where the spermatozoa are delivered.…”
Section: Delivery Of Male Secretions To the Vaginamentioning
confidence: 99%